Planetary cycloid roller gear reducer - Phuc, Nguyen Thien (Vietnam Journal of Mechanics, 2002)
In this paper we present some results of the shaping tooth profile and the method of the relationships between gear parameters and of the analysis for properties of the planetary cycloid roller gear reducer.